Immediate-release/extended-release amantadine (OS320) to treat Parkinson's disease with levodopa-induced dyskinesia: Analysis of the randomized, controlled ALLAY-LID studies. (March 2022) - Rascol, Olivier; Tönges, Lars; deVries, Tina; Jaros, Mark; Quartel, Adrian; Jacobs, David; ,; Azulay, Jean-Philippe; Balaguer, Ernest; Bhatia, Perminder; Bodis-Wollner, Ivan; Brownstone, Paul; et al.
Abstract: Background: Immediate-release (IR) amantadine has been used for treatment of levodopa induced dyskinesia (LID). The immediate-release/extended-release (IR/ER) amantadine formulation OS320 (OSMOLEX ER®) contains an IR outer layer and ER core for once-daily dosing. Objective: Report individual and pooled results for the similarly designed double-blind, placebo-controlled ALLAY-LID I and II trials, assessing IR/ER-amantadine for LID. Methods: PD patients with LID were randomized to IR/ER-amantadine 193 mg, 258 mg, or placebo. Primary endpoint was Unified Dyskinesia Rating Scale (UDysRS) score change from baseline to Day 98. Secondary outcome was ON time without troublesome dyskinesia based on diaries. Exploratory outcomes were other diary states (including OFF), MDS-UPDRS Parts II + III and Fatigue Severity Scale. Results: Overall, 222 individuals enrolled (N = 87 ALLAY-LID I, N = 135 ALLAY-LID II); both trials terminated early for sponsor's decision. While ALLAY-LID I did not meet its primary endpoint, a significant reduction in UDysRS scores versus placebo was observed in ALLAY-LID II for both 193 mg and 258 mg doses. In the pooled analysis, placebo-adjusted UDysRS score differences were −5.5 [−9.8, −1.2], p = 0.012 and −5.2 [−9.5, −0.9], p = 0.017, respectively. IR/ER-amantadine 258 mg significantly increased time spent ON without troublesome dyskinesia in ALLAY-LID II and pooled analysis. Reductions in ON time with dyskinesia supported the primary outcome. There was no effect on OFF time or other outcomes. Overall, 13.3% (193 mg), 18.7% (258 mg) and 11.1% (placebo) discontinued for adverse events, most commonly hallucinations (4.0%, 10.7%, and 1.4%, respectively). Conclusions: IR/ER-amantadine significantly reduced LID in ALLAY-LID II but not in ALLAY-LID I; post-hoc pooled data also indicated a positive treatment effect on LID. Highlights: Immediate release amantadine has been used to treat levodopa induced dyskinesia. OS320 (immediate/extended release amantadine) allows once-daily dosing. In pooled analysis of 2 trials, OS320 significantly reduced dyskinesia vs placebo. There was no significant effect on OFF time. OS320 had a safety profile consistent with other amantadine formulations.